2016
DOI: 10.1111/vec.12540
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an oral direct factor Xa inhibitor anticoagulant in healthy adult horses

Abstract: At the low end of the recommended dose in people this oral formulation of DiXaI did not reach prophylactic plasma antifactor Xa activity in this group of healthy adult horses. Further studies are warranted in order to establish the prophylactic dose for horses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In terms of peak time, peak plasma activity of rivaroxaban was reached 2‐4 hours after administration in humans . We selected 3 hours post‐administration as the peak time point according to previous studies in humans . A recent study reported a peak time point of 1.5‐2 hours after dosing in dogs .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of peak time, peak plasma activity of rivaroxaban was reached 2‐4 hours after administration in humans . We selected 3 hours post‐administration as the peak time point according to previous studies in humans . A recent study reported a peak time point of 1.5‐2 hours after dosing in dogs .…”
Section: Discussionmentioning
confidence: 99%
“…29 We selected 3 hours post-administration as the peak time point according to previous studies in humans. 10,22 A recent study reported a peak time point of 1.5-2 hours after dosing in dogs. 14 However, the dogs in our study were not allowed to fast during the study period; thus, the peak time may have been slightly delayed because food can interfere with the absorption of rivaroxaban, leading to delayed peak times of 0.5-1.5 hours compared to those in the fasted state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An unidentified direct oral anti-Xa inhibitor was administered to nine horses at a dose of 0.125 mg/kg PO at 24 h intervals for 4 days, however prophylactic anti-Xa activity was detected in only one animal after the first dose (32). To our knowledge, apixaban has not yet been tested in horses.…”
Section: Introductionmentioning
confidence: 99%